If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-3x + 6) = 126 Reorder the terms: 7(6 + -3x) = 126 (6 * 7 + -3x * 7) = 126 (42 + -21x) = 126 Solving 42 + -21x = 126 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -21x = 126 + -42 Combine like terms: 42 + -42 = 0 0 + -21x = 126 + -42 -21x = 126 + -42 Combine like terms: 126 + -42 = 84 -21x = 84 Divide each side by '-21'. x = -4 Simplifying x = -4
| 5+-1(t+3)=-1+2(t-3) | | 6(-2)+24=-12y | | 7(-3+6)=126 | | 3a+4x=c | | 64+9f=793 | | x=2y^2-3 | | r+16=20 | | x(1/x+2)=14 | | 9-x=3x+7 | | 117-9r=36 | | 138=6(5r-2) | | 2(3x+5)-2(3x-2)=8 | | 3/2(x)-1/2=x+7/6 | | u/31+587=597 | | 172=-4(8x-3) | | 178-6u=940 | | xy-5x-5y-7=0 | | 2x+12+2x+4x=180 | | -2.11=x-3.7-6.3x | | 6x+47=8x*31 | | (11x+1)(8y+9)=14 | | 4x^2+bx+24=0 | | 6m*6m*6m=0 | | 30=-5(6n+5) | | -32=-6(3s+9) | | 4.2=a+6.4+1.1 | | -16x^2+143x+9=0 | | 13x-20=5x+36 | | x^2+50x+464=0 | | 1n+2n=6 | | -16x^2+143t+9=0 | | 1n+2n=5 |